Using Virtual Reality in the Classroom: Reflections of STEM Teachers on the Use of Teaching and Learning Tools - Bekir Yildirim; Emine Sahin-Topalcengiz; Gokhan Arikan; Serkan Timur (Journal of Education in Science, Environment and Health)
The purpose  of the study was to determine teachers’ opinions about virtual reality (VR). Virtual Reality Interview Form (VRIF) administered to seven teachers after the implementation of VR practices. Teachers received three weeks of intensive training. Afterward, teachers applied VR for two months in their classrooms. Later, interviews held with them. Findings indicated that different VR practices, including Google Cardboard, were used in the classroom. According to the teachers, using virtual reality in the classroom captured students’ interest, increased their creativity, allowed students to take virtual trips, increased students’ motivation, improved students’ technology literacy, individualized learning; made students easier to understand difficult concepts. The potential problems of using VR were not asked the teachers; however, teachers mentioned that online safety and security, student access, and technology gaps were the problems they faced. The findings of this study suggest that the use of VR allows teachers to visualize abstract topics and enrich instruction. A VR orientation module would be provided teachers with opportunities to learn, practice, and apply their VR skills before being placed in the classroom.